2015
DOI: 10.1016/j.jocd.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Diagnostic Accuracy of Kellgren-Lawrence Grading for Osteoarthritis Using Radiographs and Dual-Energy X-ray Absorptiometry Images

Abstract: Advances in image quality from modern dual-energy X-ray absorptiometry (DXA) scanners now allow near radiograph-like quality images at a low radiation dose. This opens potential new applications for the use of DXA scanners to study other musculoskeletal conditions, such as osteoarthritis, which is often investigated by visual assessment of radiographs. Together, osteoporosis and osteoarthritis are the 2 most common musculoskeletal conditions, both of which primarily affect older people. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Precision of KL grading was determined in a previous study using quadratic-weighted kappa (QWK) with an intraobserver repeatability for this reader of 0.88 and interobserver repeatability of 0.81 against a radiologist with more than 10 years' experience. 37 For analysis, KLG0 and 1 were combined, as were KLG3 and 4. Table 1 shows the groups and results of tests for differences in the distribution of radiographic severity with sex, age, and body mass index (BMI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision of KL grading was determined in a previous study using quadratic-weighted kappa (QWK) with an intraobserver repeatability for this reader of 0.88 and interobserver repeatability of 0.81 against a radiologist with more than 10 years' experience. 37 For analysis, KLG0 and 1 were combined, as were KLG3 and 4. Table 1 shows the groups and results of tests for differences in the distribution of radiographic severity with sex, age, and body mass index (BMI).…”
Section: Resultsmentioning
confidence: 99%
“…While it provides initial data on possible associations between marrow fractional-fat content and OA severity, a longitudinal study would be needed to show whether more subtle changes could be detected in individuals with the incidence and progression of OA. Radiographs were graded by only one reader, not directly involved in this study, which may have led to some ROA cases being misclassified, although calibration in previous studies showed intra-and interobserver repeatability for this reader 37 to fall into the "almost perfect" (QWK !0.81) as defined by Landis and Koch. 45 Study numbers are also relatively small, especially in the KLG2 and 4 groups, and when further subdivided by sex led to some results being close to, but greater than, traditional measures denoting significance.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether associations between walking age and hip shape were secondary to OA, DXA images were graded for hip OA and assigned Kellgren‐Lawrence grades as previously described . Associations between walking age and OA were assessed in the whole cohort, then associations between walking age and hip shape modes were repeated in only the 707 individuals with no evidence of OA.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Both points were demonstrated in a recent study by Kolta et al [80] in which 1254 postmenopausal women in the European OPUS cohort, mean age 67 years, underwent TBS measurement at baseline and again at a mean of six years later. The severity of spinal osteoarthritis was graded according to Kellgren and Lawrence [81]. The investigators found that TBS was no different in women with, versus without, osteoarthritic changes in the spine at baseline, while lumbar spine aBMD measurements averaged 5.7% higher in the former group (p< 0.003).…”
Section: Osteoarthritismentioning
confidence: 99%